Anthocyanins in Mulberry Leaves (Morus rubra L.) Ethanol Extract as the Inhibitor for the Growth of Candida albicans - Nina Hidayatunnikmah; Anik Latifah; Desta Ayu Cahya Rosyida (EMBRIO: Jurnal Kebidanan, 2023)
Infections caused by Candida albicans are generally common in the vaginal mucosa or called Vulvovaginal Candidiasis. Herbal medicine is proven to be an alternative to treat vaginal candidiasis. Mulberry leaves have many chemical compounds, one of which is anthocyanins. Anthocyanins have pharmacological benefits and biological activity that can protect against human pathogenic bacteria. This study aims to observe the effect of anthocyanin compounds extracted from mulberry leaves (Morus Rubra L) on the growth of Candida albicans. Identification of compounds on mulberry leaves used the TLC spectrophotodensitometry on silica gel 60 F254. TLC plates were washed with methanol and activated at 110 degrees C for 30 minutes. The plates were eluted in a chamber that had been saturated with the mobile phase of n-butanol:glacial acetic acid:water (4:1:2) and transferred using a CMAG TLC densitometer with a spectrum in the wavelength range of 200-700 nm. Design study is experimental study with a short Post-Test Only Control Group. This study was conducted at the Pharmaceutical Biology Laboratory of PGRI Adi Buana University and the Laboratory of Professor Nidhom Foundation. The results showed that there was a content of anthocyanin compounds in mulberry leaves with antifungal function against Candida albicans.